Case study of colorectal endometriosis treated with endoscopic submucosal excavation - Xu, Tangzhou; Qiu, Bingfeng; Xu, Qi; Qu, Junhan; Zhuang, Dandan; Xu, Qiancheng (Frontiers in Physiology, 2023)
Colorectal endometriosis (CEM) is a rare and complicated form of deep invasive endometriosis. Its treatment methods include drug therapy and surgery. However, it is often difficult to alleviate symptoms and address problems, such as infertility, using drug treatment alone. Surgical intervention provides a histologic diagnosis, allows assessment of pelvic cysts or masses with features concerning for malignancy, and reduces pain by destroying the endometriotic implants. We consider surgery in women with the following: Persistent pain despite medical therapy; Contraindications to or refusal of medical therapy; Need for a tissue diagnosis of endometriosis; Exclusion of malignancy in an adnexal mass; Obstruction of the bowel or urinary tract. But there is no consensus about the surgical methods. With the rapid development of gastroenteroscopy technology in recent years, many local gastrointestinal tumors that previously required surgical resection can now be removed by endoscopic surgery. Herein, we report one case of CEM treated by endoscopic submucosal excavation (ESE) to provide a new treatment option for the radical resection of single CEM.